Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.2 - Negative Exponents and Scientific Notation - Exercise Set: 55



Work Step by Step

$\frac{3^{-1}x^{4}}{3^{3}x^{-7}}=\frac{3^{-1}}{3^{3}}\times\frac{x^{4}}{x^{-7}}=3^{-1-3}\times x^{4-(-7)}=3^{-4}\times x^{4+7}=3^{-4}\times x^{11}=\frac{x^{11}}{3^{4}}=\frac{x^{11}}{81}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.